2003
DOI: 10.1080/1364253031000136376
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the Cladophorophyceae (Chlorophyta) inferred from partial LSU rRNA gene sequences: is the recognition of a separate order Siphonocladales justified?

Abstract: Phylogenetic relationships within the green algal class Cladophorophyceae were investigated. For 37 species, representing 18 genera, the sequences of the 5'-end of the large subunit rRNA were aligned and analysed. Ulvafasciata and Acrosiphonia spinescens (Ulvophyceae) were used as outgroup taxa. The final alignment consisted of 644 positions containing 208 parsimony-mformative sites. The analysis showed three lineages within the Cladophorophyceae: Cladophora horii diverged first, followed by two main lineages.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 35 publications
4
51
0
8
Order By: Relevance
“…The Cladophorales (including Siphonocladales) comprises four main lineages, likely from a filamentous marine ancestor (Bakker et al, 1994;Hanyuda et al, 2002;Leliaert et al, 2003;Leliaert et al, 2009a). The marine unbranched, microfilamentous Okellya forms the earliest diverging lineage, followed by the Aegagropila clade, which is often found in highly specialized freshwater habitats (e.g., lake-balls or epizoophytes on turtles and snails).…”
Section: Ulvophyceaementioning
confidence: 99%
“…The Cladophorales (including Siphonocladales) comprises four main lineages, likely from a filamentous marine ancestor (Bakker et al, 1994;Hanyuda et al, 2002;Leliaert et al, 2003;Leliaert et al, 2009a). The marine unbranched, microfilamentous Okellya forms the earliest diverging lineage, followed by the Aegagropila clade, which is often found in highly specialized freshwater habitats (e.g., lake-balls or epizoophytes on turtles and snails).…”
Section: Ulvophyceaementioning
confidence: 99%
“…Consequently, Cladophora section Basicladia has no nomenclatural standing, even though the species fall within van den Hoek's concept of the genus. Thus, while van den Hoek's morphological concept of the genus Cladophora as including Basicladia may be reasonable, Cladophora is a polyphyletic grouping that includes several well-characterized genera (Leliaert et al 2003). Cladogram topology suggests that Basicladia will be maintained as a generic segregate within a multigeneric Cladophoraceae (Yoshii et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The proximity of C. rupestris with the genus Chaetomorpha has been reported in previous papers (Bakker et al 1994, Hanyuda et al 2002. Cladophora rupestris grouped with Chaetomorpha species in the ML analysis inferred from LSU rDNA carried out by Leliaert et al (2003) indicating that, as suggested by Hoek (1982), Chaetomorpha could be considered as a reduced form and not as a primitive sister genus of Cladophora.…”
Section: Discussionmentioning
confidence: 73%
“…(Cladophorales, Chlorophyta) is composed by a heterogeneous group of species that shows a high morphological plasticity infl uenced by thallus age and habitat. The genus is widespread in marine, freshwater, estuarine and brackish water environments, from temperate to tropical regions (Hoek 1963, Dodds & Gudder 1992, Hoek et al 1995, Hoek & Chihara 2000, Leliaert et al 2003). Taxonomical problems due to morphological plasticity and wide geographical distribution led to the use of molecular biology analyses to study the genus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation